PROFITABILITAS, LEVERAGE, DAN DIVIDEN TERHADAP NILAI PERUSAHAAN PROPERTI DAN REAL ESTATE DI INDONESIA - Bastian, M; Suwarno, Try Edi; Alfikri, Rahmatullah; Amirah, Shahnaz Arianne (KINDAI, 2025)
Abstract: This study analyzes the effect of Profitability, leverage, and Dividend Policy on Firm Value in the property and real estate sector listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach with an associative research design was employed using secondary data from annual financial reports of 37 companies selected through purposive sampling. The research variables include Profitability (ROA), leverage (DER), Dividend Policy (DPR), and Firm Value (Tobin’s Q). Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that ROA, DER, and DPR have a positive and significant effect on Firm Value. The R-Square value of 0.170 indicates that the independent variables explain 17% of the variation in Firm Value. These findings support the Signaling Theory, suggesting that financial information provides positive signals to investors. Keywords: profitability, leverage, dividend policy, firm value